Subharmonic functions of finite (γ,ε) -type in a half-plane - K. G. Malyutin; I. I. Kozlova (Математичні Студії)
We obtain criterions for delta-subharmonic function to belong to the class of functions of finite (γ,ε) )-type in a half-plane. These criterions are formulated in terms of Fourier coefficients of a function.